Regulation of Muscle Stem Cell Function by the Transcription Factor Pax7 - Pasut, Alessandra (Université d'Ottawa / University of Ottawa, 2015)
Pax7 is a paired box transcription factor expressed by all satellite cells which are critically required for muscle regeneration and growth. The absolute requirements of Pax7 in the maintenance of the satellite cell pool are widely acknowledged. However the mechanisms by which Pax7 executes muscle regeneration or contributes to satellite cell homeostasis remain elusive. We performed cell and molecular analysis of Pax7 null satellite cells to investigate muscle stem cell function. Through genome wide studies, we found that genes involved in cell cell interactions, regulation of migration, control of lipid metabolism and inhibition of myogenic differentiation were significantly perturbed in Pax7 null satellite cells. Analysis of satellite cells in vitro showed that Pax7 null satellite cells undergo precocious myogenic differentiation and have perturbed expression of genes involved in the Notch signaling pathway. We showed that Notch 1 is a novel Pax7 target gene and by using a genetic approach we demonstrated that ectopic expression of the constitutively active intracellular domain of Notch1 (NICD1) in Pax7 null satellite cells is sufficient to maintain the satellite cell pool as well as to restore their proliferation. Instead of differentiating into myogenic cells and in the absence of a myogenic cue, NICD1 Pax7 null satellite cells become a source of ectopic brown fat within muscles and give rise to brown adipocytes both in vivo and in vitro. In conclusion we showed that Notch 1 partially rescues Pax7 deficient satellite cells loss and proliferation. Additionally we provide the first evidence that Notch signalling contributes to satellite cell fate by inhibiting terminal myogenic differentiation and inducing brown adipogenesis.
Keywords: Pax7; Notch signaling; satellite cells